2014
DOI: 10.1007/s10464-014-9683-x
|View full text |Cite
|
Sign up to set email alerts
|

Academic and Social Integration on Campus Among Sexual Minority Students: The Impacts of Psychological and Experiential Campus Climate

Abstract: A heterosexist campus climate can increase risk for mental health problems for sexual minority students; however, the relationship between campus climate for sexual minorities and academic outcomes remains understudied. Using a sample of sexual minority respondents extracted from a campus climate survey conducted at a large university in the Midwest, we examine relationships between multiple dimensions of psychological and experiential campus climate for sexual minorities with academic integration (academic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(129 citation statements)
references
References 38 publications
4
124
0
1
Order By: Relevance
“…It is not clear to what extent LGBTQ students may struggle academically in comparison to others, but scholars have noted the particularly hostile climate LGBTQ students face (Rankin 2005;Rankin et al 2010;Woodford, Han et al 2014;Woodford, Kulick et al 2014), fulfilling at least half of Choy's definition for high risk of attrition. This study builds on recent studies exploring LGBTQ students' perceptions of faculty (Garvey and Inkelas 2012) and the link between instructor relations and students' academic outcomes and social integration (Woodford and Kulick 2015) by shedding light on how faculty are sources of support for this potentially at-risk group. This study bears implications primarily for practice, policy, and future research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is not clear to what extent LGBTQ students may struggle academically in comparison to others, but scholars have noted the particularly hostile climate LGBTQ students face (Rankin 2005;Rankin et al 2010;Woodford, Han et al 2014;Woodford, Kulick et al 2014), fulfilling at least half of Choy's definition for high risk of attrition. This study builds on recent studies exploring LGBTQ students' perceptions of faculty (Garvey and Inkelas 2012) and the link between instructor relations and students' academic outcomes and social integration (Woodford and Kulick 2015) by shedding light on how faculty are sources of support for this potentially at-risk group. This study bears implications primarily for practice, policy, and future research.…”
Section: Discussionmentioning
confidence: 99%
“…They found that "LGB students, on average, reported significantly higher rates of satisfaction with faculty and staff interactions than [did] heterosexual students" (179). In another study, Woodford and Kulick (2015) found that more positive instructor relations were associated with higher selfreported grade point average, classroom engagement, social acceptance on campus, and institutional satisfaction, even when considering heterosexist harassment and psychological climate; however, instructor relations did not protect students from the negative effects of heterosexism. These studies, while illuminating, did not include transgender students.…”
Section: Language Usagementioning
confidence: 93%
See 2 more Smart Citations
“…Representations of LGBTQA+ lives should move beyond acceptance and tolerance toward celebration and inclusion. Such representations may engender a sense of belonging and acceptance of LGBTQA+ people not only in an individual program but across the campus climate (Woodford & Kulick, 2014). Conducting an audit of all current communications, programs, and services-as well as being mindful in creating new ones-can contribute to positive climate.…”
Section: Representing Lgbtqa+ Lives Across the College Life Cyclementioning
confidence: 99%